Body mass index in the institionalised elderly people in Rumah Sri Kenangan - Wan Su, Kamaruzaman (University Sains Malaysia, 1997)
Anthropometric measurements of weight, height and body mass index was taken from 34 institutionalised elderly people, consisting of 24 male and 10 female, aged 55 to 90 years (mean 69.3 years), 20 Malay, 7 Chinese and 7 Indian, at Rumah Sri Kenangan Kelantan. The prevalence of low BMI (<20.0 kg/m2) was 50.0% and 17.6% of them had BMI below 17.5 kg/m2. There was no significant difference in the prevalence of low BMI between age (old and young elderly), gender (male and female) and ethnicity (Malay, Chinese and Indian). It can be concluded that the institutionalised elderly are suffering from chronic energy deficiency or subclinical malnutrition.